BELAJAR PENDIDIKAN KARAKTER DARI SUNDA ( STUDI PADA KEPEMIMPINAN OTISTA) - Dedi Epriadi (Ekonomis: Journal of Economics and Business, 2017)
This research aims to lead by example leadership of Oto Iskandar DiNata sunda, in the midst of a crisis of character giving the leadership at this time. Using historical and qualitative approach method. The results of research that the establishment of theleadership character is influenced by the background of social, cultural, political, and linguistic typology leadership in Sundanese perspective ranging from To, Hookeun, Mukpruk, Ngulas so dapatdisarikan in leadership today's modern so that it can be utilized by current younger generation about lead by example from an Oto Iskandar DiNata.Key Words: Kepemimimpinan, Sundanese, Oto Iskandar DiNata